Trends in microbiological profiles and antibiotic resistance in periprosthetic joint infections. Issue 3 (March 2021) - Hu, Lifeng; Fu, Jun; Zhou, Yonggang; Chai, Wei; Zhang, Guoqiang; Hao, Libo; Chen, Jiying
Objective: This study examined the trends in demographics, the distribution of microorganisms, and antibiotic resistance in patients with periprosthetic joint infection (PJI). Methods: We conducted a retrospective study of 231 consecutive patients diagnosed with PJI in our hospital from January 2006 to December 2015 (93 and 138 patients diagnosed in 2006–2010 and 2011–2015, respectively). The linear-by-linear chi-squared test was used to assess the trends in demographics, the distribution of microorganisms, and antibiotic resistance. Results: Gram-positive cocci accounted for 63.9% of all pathogens, and coagulase-negative Staphylococcus (CoNS) accounted for 38.1% of all isolates. The proportion of isolates identified as methicillin-resistant CoNS significantly increased over the study period (39.0% vs. 61.8%). In addition, the proportions of levofloxacin-resistant CoNS (4.9% vs. 21.8%) and Staphylococcus aureus (6.3% vs. 45.0%) isolates significantly increased over the study period. By contrast, the proportions of penicillin-resistant CoNS (82.9% vs. 40.0%) and S. aureus (75.0% vs. 30.0%) isolates decreased over the study period. Conclusion: Our research revealed changes in the distribution of microorganisms and antibiotic resistance profile of the pathogens responsible for PJI over time, which could complicate treatment. These findings may serve as a reference for strategies to prevent and empirically treat PJI in China.